Comprehensive analysis of ceRNA network composed of circRNA, miRNA, and mRNA in septic acute kidney injury patients based on RNA-seq - Si-Rong Ma; Qi Ma; Ya-Nan Ma; Wen-Jie Zhou; Wen-Jie Zhou (Frontiers in Genetics, 2023)
Background: Sepsis is a complex, life-threatening clinical syndrome that can cause other related diseases, such as acute kidney injury (AKI). Circular RNA (circRNA) is a type of non-coding RNA with a diverse range of functions, and it plays essential roles in miRNA sponge. CircRNA plays a huge part in the development of various diseases. CircRNA and the competing endogenous RNA (ceRNA) regulatory network are unknown factors in the onset and progression of septic AKI (SAKI). This study aimed to clarify the complex circRNA-associated regulatory mechanism of circRNAs in SAKI.Methods: We collected 40 samples of whole blood of adults, including 20 cases of SAKI and 20 cases of healthy controls. Moreover, five cases were each analyzed by RNA sequencing, and we identified differentially expressed circRNA, miRNA, and mRNA (DEcircRNAs, DEmiRNAs, and DEmRNAs, respectively). All samples were from SAKI patients with intraperitoneal infection.Results: As a result, we screened out 236 DEcircRNAs, 105 DEmiRNAs, and 4065 DEmRNAs. Then, we constructed two co-expression networks based on RNA–RNA interaction, including circRNA–miRNA and miRNA–mRNA co-expression networks. We finally created a circRNA–miRNA–mRNA regulation network by combining the two co-expression networks. Functional and pathway analyses indicated that DEmRNAs in ceRNA were mostly concentrated in T cell activation, neutrophils and their responses, and cytokines. The protein–protein interaction network was established to screen out the key genes participating in the regulatory network of SAKI. The hub genes identified as the top 10 nodes included the following: ZNF727, MDFIC, IFITM2, FOXD4L6, CIITA, KCNE1B, BAGE2, PPIAL4A, USP17L7, and PRSS2.Conclusion: To our knowledge, this research is the first study to describe changes in the expression profiles of circRNAs, miRNAs, and mRNAs in patients with SAKI. These findings provide a new treatment target for SAKI treatment and novel ideas for its pathogenesis.